The Role of Gibberellins in Regulation of Nitrogen Uptake and Physiological Traits in Maize Responding to Nitrogen Availability - Wang, Yubin (Int J Mol Sci, 2020)
Modified gibberellin (GA) signaling leads to semi-dwarfism with low nitrogen (N) use efficiency (NUE) in crops. An understanding of GA-mediated N uptake is essential for the development of crops with improved NUE. The function of GA in modulating N uptake capacity and nitrate (NO(3)(−)) transporters (NRTs) was analyzed in the GA synthesis-deficient mutant zmga3ox grown under low (LN) and sufficient (SN) N conditions. LN significantly suppressed the production of GA(1), GA(3,) and GA(4), and the zmga3ox plants showed more sensitivity in shoots as well as LN stress. Moreover, the higher anthocyanin accumulation and the decrease of chlorophyll content were also recorded. The net NO(3)(−) fluxes and (15)N content were decreased in zmga3ox plants under both LN and SN conditions. Exogenous GA(3) could restore the NO(3)(−) uptake in zmga3ox plants, but uniconazole repressed NO(3)(−) uptake. Moreover, the transcript levels of ZmNRT2.1/2.2 were downregulated in zmga3ox plants, while the GA(3) application enhanced the expression level. Furthermore, the RNA-seq analyses identified several transcription factors that are involved in the GA-mediated transcriptional operation of NRTs related genes. These findings revealed that GAs influenced N uptake involved in the transcriptional regulation of NRTs and physiological responses in maize responding to nitrogen supply.